2014
DOI: 10.3389/fneur.2014.00059
|View full text |Cite
|
Sign up to set email alerts
|

Lack of C9orf72 Repeat Expansion in Taiwanese Patients with Mixed Neurodegenerative Disorders

Abstract: Background: The hexanucleotide repeat expansion in intron 1 of the C9orf72 gene is recognized as the most common genetic cause of frontotemporal dementia (FTD). There are overlapping clinical and pathological characteristics between FTD and Parkinsonism syndrome, and some FTD patients may present with Parkinsonism. The aim of this study was to analyze the hexanucleotide repeat numbers of C9orf72 gene in a mixed Taiwanese cohort with FTD, Parkinsonism syndrome, Parkinson’s disease (PD), and Alzheimer’s dementia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…The inclusion of baseline genomics data in such a cluster analyses could result in the identification of even more homogenous sets of MCI subgroups. One of the most important genetic subgrouping that has been relatively overlooked in the laboratory study of AD is the effect of gender – most rodent studies have been in male mice and only a small number of biomarker studies have tested for sex differences 6, 7 . Our analyses show that rapid MCI decliners in both sexes had worse baseline cognition, higher levels of cortical amyloid and tau pathology as well as smaller volumes of hippocampal and entorhinal cortices.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The inclusion of baseline genomics data in such a cluster analyses could result in the identification of even more homogenous sets of MCI subgroups. One of the most important genetic subgrouping that has been relatively overlooked in the laboratory study of AD is the effect of gender – most rodent studies have been in male mice and only a small number of biomarker studies have tested for sex differences 6, 7 . Our analyses show that rapid MCI decliners in both sexes had worse baseline cognition, higher levels of cortical amyloid and tau pathology as well as smaller volumes of hippocampal and entorhinal cortices.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study found that the age-specific risk of AD was almost two-fold greater in women than men (17.2% versus 9.1% at age 65 years and 28.5% versus 10.2% at age 75 years) 8 and some other studies find that sex-differences become most prominent among eighty year olds 7 . Potential mechanisms to explain such differences include greater effects of the Apolipoprotein E4 allele in women, sex hormones (such as estrogen), lower cognitive reserve, and differences in occupational or educational attainment (reviewed in refs 6 and 7. Sex differences in immune system responsivity, MRI brain atrophy rates 9 and effects of plaque-tangle pathology 10 have also been reported.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations